An introduction to public private partnership (PPP) and private finance initiative (PFI) - Said, Rasanubari Asmarah; Samsudin, Adlin (Pejabat Penasihat Undang-Undang, 2016)
PFI was initially developed in Australia and United Kingdom as a mean to deliver public sector infrastructure or services by using private sector capacity and public resources. PFI expanded in the United Kingdom in 1996. The main factor for this growth was because the UK government was under pressure to reduce public debt but at the same time, there was a high demand for better services in public assets such as hospitals, schools and roads. In Malaysia, PPP/PFI was introduced under the Ninth Malaysia Plan (2006-2010) as another mode of government project procurement and to enhance the effectiveness of the privatization program. The implementation of PPP/PFI was accelerated in the current Tenth Malaysian Plan (2011-2015) which aimed to improve the living standards of Malaysians 1 . The Tenth Malaysia Plan allocated RM20 billion to a facilitation fund to assist private sector involvement in PPP projects.